The Power of Balanced Nutrition: Fueling Your Body the Right Way - Edi Ilham (JHN: Journal of Health and Nursing, 2024)
Balanced nutrition is fundamental to maintaining overall health and well-being. The article The Power of Balanced Nutrition: Fueling Your Body the Right Way explores the significance of providing the body with the essential nutrients it needs to function optimally. By understanding the roles of macronutrients (proteins, fats, and carbohydrates) and micronutrients (vitamins and minerals), individuals can make informed choices about their diet. The article highlights the importance of incorporating a variety of whole foods, such as fruits, vegetables, lean proteins, and whole grains, to achieve a well-rounded and nutrient-dense diet. Additionally, it discusses the impact of hydration, meal timing, and mindful eating on energy levels, weight management, and long-term health. Ultimately, the article encourages readers to adopt a balanced approach to nutrition for sustained vitality and a healthier lifestyle.